Preparation method and application of composite scaffold for promoting bone defect repair after bone tumor operation
Compound scaffolds were prepared by combining nano-hydroxyapatite modified and cRGDfk-PEG2K-DSPE modified copper-cysteine nanoparticles on bone defect 3D printed scaffolds, which solved the tumor elimination and in the prior art. The defects in osteogenesis and sequencing treatment have achieved efficient drug delivery and bone defect repair.
Patent Information
- Application Number
- CN202411586603.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, 3D printed stents of bone defects have defects in eliminating tumors and promoting osteogenesis and are difficult to play a specific role in two different stages.
The polylactic acid 3D printed scaffold (PH) modified with nano-hydroxyapatite and cRGDfk-PEG2K-DSPE modified copper-cysteine nanoparticles (CCP) were prepared by the use of photoinitiators and hydrogels. Composite bracket. This composite stent quickly releases drugs in the tumor microenvironment, slowly releases them after killing the tumor, achieving bone defect repair.
The sequence treatment in the tumor elimination and osteogenesis stages is achieved, the drug delivery efficiency and bone defect repair effect are improved, and the biocompatibility and dispersion are achieved.
Smart Images

Figure CN119424735A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical stents, and in particular to a preparation method and application of a composite stent for promoting the repair of bone defects after bone tumor surgery. Background Art
[0002] Osteosarcoma originates from mesenchymal cells in the bone and is the most common primary malignant bone tumor. It often occurs in children and adolescents, causing patients to suffer from impaired motor function or even death. In surgical treatment, in order to prevent tumor recurrence, doctors must extend the resection margin to achieve the ideal R0 resection rate. However, this large area of bone tissue resection will lead to large bone defects, which cannot be repaired by autologous transplantation. In addition, even after surgical resection of all visible tumors, the probability of local recurrence is still as high as 10%.
[0003] In medical treatment, the use of systemic chemotherapy drugs can bring many side effects. Therefore, 3D scaffolds that can achieve local drug delivery have become a research hotspot. This treatment strategy often requires killing residual tumor tissue in the early stage and playing a continuous role in promoting bone formation in the later stage of treatment. However, few scaffolds can play a specific role in these two different stages. Summary of the invention
[0004] 1. Technical problems to be solved
[0005] The purpose of the present invention is to solve the defects of the prior art 3D printed scaffolds for bone defects in the sequential treatment of eliminating tumors and promoting bone formation, and to propose a preparation method and application of a composite scaffold for promoting bone defect repair after bone tumor surgery.
[0006] 2. Technical solution
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a composite scaffold for promoting the repair of bone defects after bone tumor surgery comprises the following steps:
[0009] Step 1: Preparation of nanohydroxyapatite-modified polylactic acid 3D printed scaffold (PH);
[0010] Step 2: cRGD fk -PEG 2K - Preparation of DSPE-modified copper-cysteine nanoparticles (CCP);
[0011] Step 3: Preparation of methacrylate gelatin GelMA;
[0012] Step 4: dissolving the CPP and photoinitiator prepared in step 2 in deionized water, and dissolving the GelMA prepared in step 3 into the above solution to obtain solution 1;
[0013] Step 5: Dispersing borax and sodium alginate SA in deionized water to obtain solution 2;
[0014] Step 6: Mix solution 1 with solution 2 in a stirring state to obtain solution 3 after mixing evenly;
[0015] Step 7: Fill the solution prepared in step 6 into the PH scaffold prepared in step 1, and expose the scaffold to ultraviolet light to solidify the hydrogel to form a composite scaffold.
[0016] Preferably, the step 1 is specifically:
[0017] Step 1.1: First, use an extruder to melt and extrude the PLA powder, and stretch it at an appropriate speed of 40-50 mm / s to obtain a filament with a diameter of 1.75 mm;
[0018] Step 1.2: Then, the PLA filament was heated to a set temperature of 215 °C in an electric field-driven biological 3D printer BIO-EM3DP15A and extruded through a 100-1000 μm nozzle at a speed of 6-10 mm / s to fabricate the PLA scaffold;
[0019] Step 1.3: Rinse the scaffold three times with deionized water to remove surface impurities, put the scaffold into a vacuum oven at 60 °C to dry, and then cut it into cylindrical scaffolds with a diameter and height of 3.5 mm using a 3.5 mm punch;
[0020] Step 1.4: The scaffold was then immersed in an ammonia solution with a pH of 12.5 and magnetically stirred at room temperature; finally, the scaffold was immersed in 1% w / v nanohydroxyapatite nHA / ethanol and stirred for 1 hour, washed with deionized water, and naturally air-dried to obtain nHA-modified PLA scaffold PH, in which the molecular weight of PLA was 80KDa.
[0021] Preferably, the step 2 is specifically:
[0022] Step 2.1: Dissolve sodium hydroxide and L-cysteine in deionized water to obtain solution A;
[0023] Step 2.2: Then dissolve cupric chloride dihydrate in deionized water; add an equal volume of solution A dropwise into the cupric chloride solution, stir at 500 rpm for 5 minutes to form copper-cysteine nanoparticles, collect the precipitate by centrifugation at 6000 rpm for 3 minutes, then wash the product three times with water and anhydrous ethanol respectively, and cRGD fk -PEG 2k -DSPE was dissolved in DMSO (15 mg / mL);
[0024] Step 2.3: An equal volume of CC NPs ethanol solution (15 mg / mL) was added to the above solution, and the mixture was stirred at 4 °C for 6 h, and then centrifuged (6000 rpm, 10 min) to collect CCP; wherein the concentration of sodium hydroxide was 8 g / L, the concentration of L-cysteine was 24.2 g / L, the concentration of copper chloride dihydrate was 17 g / L, and the concentration of cRGD was 1. fk -PEG 2k -DSPE concentration was 15 mg / mL.
[0025] Preferably, the step 3 is specifically:
[0026] Step 3.1: 10% w / v pig skin gelatin was added to PBS, and the mixture was magnetically stirred at 45-55°C for 1 hour; then 8-10 mL of methacrylic anhydride (MA) was added dropwise to the gelatin solution and stirred at 50°C for 3 hours;
[0027] Step 3.2: Add an equal amount of PBS preheated to 50°C to terminate the reaction, dialyze the reaction solution in deionized water using a dialysis bag (molecular cutoff 8-14KD) for 7-10 days to remove MA, filter the solution and freeze-dry it to obtain methacrylate gelatin.
[0028] Preferably, in step 4, the concentration of CCP is 0.1-1% w / v; the concentration of borax is 1-4% w / v; the concentration of GelMA is 5-10% w / v; the concentration of sodium alginate is 4% w / v; the photoinitiator is one of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or 2,4,6-trimethylbenzoyl lithium phosphite, and the concentration of the initiator in the system is 0.1-1% w / v.
[0029] Preferably, in step 5, the concentration of borax is 2% w / v; the concentration of sodium alginate is 4% w / v; and both are stirred at 40-60° C. for 1-4 hours to completely dissolve the borax and sodium alginate in deionized water.
[0030] Preferably, in step 6, the ratio of solution 1 to solution 2 is 1:1, the stirring condition is 400 rpm, and the stirring time is 10 minutes.
[0031] Preferably, the volume of solution three used in step 7 is 15 μL, the wavelength of ultraviolet light is 300-400 nm, and the curing time is 3-5 minutes.
[0032] The present invention also proposes the use of the composite scaffold in repairing bone defects after osteosarcoma surgery.
[0033] 3. Beneficial effects
[0034] Compared with the prior art, the advantages of the present invention are:
[0035] (1) In the present invention, the outer surface of the prepared CCP nanoparticles is coated with cRGD fk -PEG 2K -DSPE, on the one hand, enhances the biocompatibility and dispersibility of nanoparticles, and on the other hand, RGD peptide can target tumor cells and improve the drug delivery efficiency.
[0036] (2) In the present invention, CCP can achieve a chemokinetic tumor killing effect triggered by high glutathione and high hydrogen peroxide in tumor cells, and at the same time it can consume GSH to enhance the copper death effect. The copper ions in CCP can also promote the osteogenic differentiation of mesenchymal stem cells, thereby promoting bone defect repair.
[0037] (3) In the present invention, the pH scaffold in the prepared composite scaffold provides osteogenesis and microenvironmental mechanical support, and the hydrogel (containing borate bonds) therein serves as a carrier of nanodrugs, rapidly releasing drugs in the tumor microenvironment (low pH, high ROS), and slowly releasing drugs after killing the tumor, thereby achieving sequential treatment that promotes osteogenesis after eliminating the tumor. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 AK are transmission electron microscope images, Zeta potential analysis, particle size analysis, dispersibility analysis, X-ray diffraction peak spectrum, Fourier transform infrared spectrum, and X-ray photoelectron energy spectrum of Example 1 of the present invention and Comparative Example 1 (Figure HK), respectively. Scale bars in the figure: A is 100 nm, and B is 100 nm;
[0039] Figure 2 AI are respectively a schematic diagram of the intracellular cascade reaction of Example 1 of the present invention, a general diagram of the reaction product with GSH, a fluorescence excitation diagram of the reaction product with GSH, a fluorescence intensity curve of the reaction product with GSH, a GSH consumption capacity curve, an X-ray photoelectron energy spectrum diagram of the reaction product with GSH (Figure F and Figure G), a ROS generation capacity curve (TMB detection method), and an ESR electron spin resonance spectrum diagram (DMPO capture agent);
[0040] Figure 3 AG are scanning electron images (Figures A, B and F), stress-strain curves, general diagrams of sessile drop method water contact angles, statistical diagrams of sessile drop method water contact angles, and CCP drug release curves of Example 2, Example 3 and Comparative Example 2 of the present invention, respectively. Scales in the figures: A is 500 μm (upper) and 100 μm (lower), B is 500 μm (upper) and 100 μm, and C is 500 μm (upper) and 100 μm (lower);
[0041] Figure 4Figures A and H are respectively the fluorescence images of drug phagocytosis of tumor cells, CCK8 cell viability curve, dead / live staining fluorescence images, images of inhibition of tumor cell cloning and invasion ability, and tumor cell apoptosis flow cytometry images of Example 3, Comparative Example 4, and Comparative Example 5 used in cell experiments (Figures E and H), where the scales in the figures are: A is 50 μm, C is 100 μm, and D is 100 μm;
[0042] Figure 5 AF are respectively schematic diagrams of nude mouse orthotopic osteosarcoma resection models used for in vivo experiments in Example 3, Comparative Example 4 and Comparative Example 5 of the present invention, bioluminescence images of nude mouse orthotopic bone tumors, tumor volume change curves, nude mouse weight change curves, nude mouse survival curves, and Micro-CT three-dimensional reconstruction images of nude mouse tibias;
[0043] Figure 6 AK are respectively the general image and bioluminescence image of lung metastasis of nude mice used for in vivo experiments in Example 3, Comparative Example 4 and Comparative Example 5 of the present invention, H&E staining image of lung tissue of nude mice, H&E staining image of orthotopic bone tumor of nude mice, Tunel immunofluorescence image of tumor tissue, Ki67 immunofluorescence image of tumor tissue, Dlat immunofluorescence image of tumor tissue, Fdx1 immunofluorescence image of tumor tissue, bioluminescence statistical image of lung metastasis, and immunofluorescence statistical image (Figure IK), where the scales in the figures: B are 2 mm (upper) and 150 μm (lower), respectively, C are 200 μm and 100 μm, respectively, and DG are both 150 μm;
[0044] Figure 7 AF are respectively the gross images of rat femoral condyle defect surgery used for in vivo experiments in Example 3, Comparative Example 4 and Comparative Example 5 of the present invention, the Micro-CT three-dimensional reconstruction images of rat femoral condyle, CT data statistical graphs (Figures C and D), H&E and Masson staining images of femoral condyle tissue sections (Figures E and F), and OCN and OPN immunofluorescence staining images of rat femoral condyle (Figures G and H). Scale bars in the figures: G and H are both 150 μm. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0046] A method for preparing a composite scaffold for promoting the repair of bone defects after bone tumor surgery comprises the following steps:
[0047] Step 1: Preparation of nano-hydroxyapatite modified polylactic acid 3D printed scaffold (PH); Step 1 is specifically as follows:
[0048] Step 1.1: First, use an extruder to melt and extrude the PLA powder, and stretch it at an appropriate speed of 40-50 mm / s to obtain a filament with a diameter of 1.75 mm;
[0049] Step 1.2: Then, the PLA filament was heated to a set temperature of 215 °C in an electric field-driven biological 3D printer BIO-EM3DP15A and extruded through a 100-1000 μm nozzle at a speed of 6-10 mm / s to fabricate the PLA scaffold;
[0050] Step 1.3: Rinse the scaffold three times with deionized water to remove surface impurities, put the scaffold into a vacuum oven at 60 °C to dry, and then cut it into cylindrical scaffolds with a diameter and height of 3.5 mm using a 3.5 mm punch;
[0051] Step 1.4: Then immerse the scaffold in an ammonia solution with a pH of 12.5 and stir magnetically at room temperature; finally, immerse the scaffold in 1% w / v nanohydroxyapatite nHA / ethanol and stir for 1 hour, wash with deionized water, and air dry naturally to obtain nHA-modified PLA scaffold PH, wherein the molecular weight of PLA is 80KDa;
[0052] Step 2: cRGD fk -PEG 2K - Preparation of DSPE-modified copper-cysteine nanoparticles (CCP); Step 2 is specifically:
[0053] Step 2.1: Dissolve sodium hydroxide and L-cysteine in deionized water to obtain solution A;
[0054] Step 2.2: Then dissolve cupric chloride dihydrate in deionized water; add an equal volume of solution A dropwise into the cupric chloride solution, stir at 500 rpm for 5 minutes to form copper-cysteine nanoparticles, collect the precipitate by centrifugation at 6000 rpm for 3 minutes, then wash the product three times with water and anhydrous ethanol respectively, and cRGD fk -PEG 2k -DSPE was dissolved in DMSO (15 mg / mL);
[0055] Step 2.3: An equal volume of CC NPs ethanol solution (15 mg / mL) was added to the above solution, and the mixture was stirred at 4 °C for 6 h, and then centrifuged (6000 rpm, 10 min) to collect CCP; wherein the concentration of sodium hydroxide was 8 g / L, the concentration of L-cysteine was 24.2 g / L, the concentration of copper chloride dihydrate was 17 g / L, and the concentration of cRGD was 1. fk -PEG 2k -DSPE concentration is 15mg / mL
[0056] Step 3: Preparation of methacrylate gelatin GelMA; Step 3 is specifically as follows:
[0057] Step 3.1: 10% w / v pig skin gelatin was added to PBS, and the mixture was magnetically stirred at 45-55°C for 1 hour; then 8-10 mL of methacrylic anhydride (MA) was added dropwise to the gelatin solution and stirred at 50°C for 3 hours;
[0058] Step 3.2: Add PBS preheated to 50°C in an amount equal to that of the above-mentioned mixture to terminate the reaction, dialyze the reaction solution in deionized water using a dialysis bag (molecular cutoff 8-14KD) for 7-10 days to remove MA, filter the solution and freeze-dry it to obtain methacrylate gelatin;
[0059] Step 4: dissolving the CPP and photoinitiator prepared in step 2 in deionized water, dissolving the GelMA prepared in step 3 in the above solution to obtain solution 1, wherein the concentration of CCP is 0.1-1% w / v; the concentration of borax is 1-4% w / v; the concentration of GelMA is 5-10% w / v; the concentration of sodium alginate is 4% w / v; the photoinitiator is one of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or 2,4,6-trimethylbenzoyl lithium phosphite, and the concentration of the initiator in the system is 0.1-1% w / v;
[0060] Step 5: Disperse borax and sodium alginate SA in deionized water to obtain solution 2, wherein the concentration of borax is 2% w / v; the concentration of sodium alginate is 4% w / v; stir the two at 40-60° C. for 1-4 hours to completely dissolve the borax and sodium alginate in the deionized water;
[0061] Step 6: Mix solution 1 with solution 2 in a stirring state to obtain solution 3 after mixing evenly. The ratio of solution 1 to solution 2 is 1:1. The stirring condition is 400 rpm and the stirring time is 10 minutes.
[0062] Step 7: Fill the solution three prepared in step 6 into the PH scaffold prepared in step 1, and expose the scaffold to ultraviolet light to solidify the hydrogel to form a composite scaffold. The volume of solution three used is 15 μL, the wavelength of ultraviolet light is 300-400 nm, and the curing time is 3-5 minutes.
[0063] In the present invention, the outer surface of the prepared CCP nanoparticles is coated with cRGD fk -PEG 2K -DSPE, on the one hand, enhances the biocompatibility and dispersibility of nanoparticles, and on the other hand, RGD peptide can target tumor cells and improve the drug delivery efficiency.
[0064] In the present invention, CCP can achieve the chemical dynamic tumor killing effect triggered by high glutathione and high hydrogen peroxide in tumor cells, and at the same time it can consume GSH to enhance the copper death effect. The copper ions in CCP can also promote the osteogenic differentiation of mesenchymal stem cells, thereby promoting bone defect repair.
[0065] In the present invention, the pH scaffold in the prepared composite scaffold provides osteogenesis and microenvironmental mechanical support, and the hydrogel (containing borate bonds) therein serves as a carrier of nano-drugs, rapidly releasing drugs in the tumor microenvironment (low pH, high ROS), and slowly releasing drugs after killing the tumor, thereby achieving sequential treatment that promotes osteogenesis after eliminating the tumor.
[0066] Embodiment 1:
[0067] In this example, 80 mg of sodium hydroxide and 242 mg of L-cysteine were dissolved in 10 mL of deionized water to obtain solution A. Then, 170 mg of copper chloride dihydrate was dissolved in 10 mL of deionized water. Solution A was added dropwise to the copper chloride solution using a 1 mL pipette and stirred at 500 rpm for 5 minutes to form CC NPs. After stirring, the precipitate was collected by centrifugation (6000 rpm, 3 minutes), and then washed three times with water and anhydrous ethanol respectively;
[0068] In this example, the prepared CC NPs were dispersed in ethanol and stored at 4°C for subsequent experiments. fk -PEG 2k -DSPE was used to modify the surface of CC NPs. 15 mg cRGD fk -PEG 2k -DSPE was dissolved in DMSO. 1 mL of CCNPs ethanol solution (15 mg mL -1 ) was added to the above solution. After the mixture was stirred at 4°C for 6 h, it was centrifuged (6000 rpm, 10 min) to collect the modified nanoparticles (CCP NPs), which were resuspended in 1 mL of deionized water. The prepared CC and CCP were stored at 4°C for future use.
[0069] Embodiment 2:
[0070] In this embodiment, first, PLA powder was melted and extruded using an extruder at a speed of 45 mm s -1 The PLA filament was then stretched at an appropriate speed to obtain a filament with a diameter of 1.75 mm. The PLA filament was then heated to a set temperature of 215 °C in an electric field-driven bio-3D printer (BIO-EM3DP15A) and stretched at a speed of 6–10 mm s -1The PLA scaffolds were extruded through a 250 μm nozzle at a speed of 100 μm to fabricate the PLA scaffolds. The scaffolds were rinsed three times with deionized water to remove surface impurities, dried in a vacuum oven at 60 °C, and then cut into cylindrical scaffolds with a diameter and height of 3.5 mm using a 3.5 mm punch.
[0071] In this embodiment, the scaffold was then immersed in an ammonia solution with a pH of 12.5 and magnetically stirred at room temperature (150 rpm, 30 minutes). Finally, the scaffold was immersed in 1% w / v nHA / ethanol and stirred for 1 hour, washed with deionized water, and air-dried to obtain the final PLA-nHA scaffold (PH). In addition, a scaffold with a height of 2 mm was prepared to be suitable for implantation in the tumor site of nude mice.
[0072] Embodiment 3:
[0073] (1) Preparation of GelMA: 10 g of pig skin gelatin was added to 100 mL of PBS, and the mixture was magnetically stirred at 50°C for 1 hour. Then 8 mL of methacrylic anhydride (MA) was added dropwise to the gelatin solution and stirred at 50°C for 3 hours. An equal amount of PBS preheated to 50°C was added to terminate the reaction. The reaction solution was dialyzed in deionized water using a dialysis bag (molecular cutoff 8-14KD) for 7-10 days to remove MA, and the solution was filtered and freeze-dried to obtain methacrylate gelatin;
[0074] (2) Synthesizing CPP nanoparticles according to Example 1;
[0075] (3) Preparation of GBS@CCP: 0.5 g GelMA, 10 mg LAP, and 50 mg CCP were dissolved in 5 mL deionized water to obtain solution A. 0.4 g sodium alginate and 0.2 g borax were dissolved in 5 mL deionized water and stirred at 40 °C until the sodium alginate was completely dissolved to obtain solution B. Solution A was then stirred and mixed into solution B to obtain a double cross-linked hydrogel solution (GBS@CCP);
[0076] (4) Preparation of PH-GBS@CCP: The GBS@CCP hydrogel solution was injected into the PH scaffold prepared in Example 2, and the scaffold was exposed to ultraviolet light (395 nm, LXZ919087, Guangdong, China) for 5 min to crosslink the hydrogel into a solid state, thereby forming a composite scaffold PH-GBS@CCP.
[0077] Comparative Example 1:
[0078] 80 mg of sodium hydroxide and 242 mg of L-cysteine were dissolved in 10 mL of deionized water to obtain solution A. Then, 170 mg of copper chloride dihydrate was dissolved in 10 mL of deionized water. Solution A was added dropwise to the copper chloride solution using a 1 mL pipette and stirred at 500 rpm for 5 minutes to form CC NPs. After stirring, the precipitate was collected by centrifugation (6000 rpm, 3 minutes) and then washed three times with water and anhydrous ethanol respectively. The prepared CC NPs were dispersed in ethanol.
[0079] like Figure 1 As shown in the figure, the prepared CC and CCP were characterized. Figure A and Figure B show the scanning electron microscope image and element distribution image of CC and CCP respectively; Figure C shows the cRGD fk -PEG 2K -The Zeta potential of DSPE, CC and CCP indicates that PEG is successfully coated on CC; Figure D shows the distribution curve of nanoparticle size; Figure E is an image of CC and CCP dispersed in PBS and left to stand, indicating that PEG modification improves the dispersion performance and stability of CCP; Figures F and G are XRD and FTIR spectra of CC, CCP and cysteine, indicating that CCP is successfully synthesized; Figures H and I are XPS spectra and element content diagrams of CCP, indicating that the atomic ratio of copper and sulfur in CCP is approximately 1:2; Figures J and K are XPS fine spectra and Auger spectra of copper element in CCP, indicating that copper in CCP exists in divalent form.
[0080] like Figure 2 As shown, we verified the possibility of cascade reaction of CCP in tumor cells in vitro. Figure A is a schematic diagram of the cascade reaction of CCP in cells; Figure B is the change after the reaction of CCP and GSH solution; Figure C is a picture of the product (CCP-G) after the reaction of CCP and GSH solution emitting pink fluorescence under 356nm excitation light; Figure D is the fluorescence intensity of the product after the reaction of different concentrations of CCP and GSH under 365nm excitation light; Figure E is the detection of the remaining GSH content after the reaction of different concentrations of CCP and GSH, indicating that CCP can consume GSH and is concentration-dependent; Figures F and G are the XPS copper ion fine spectrum and Auger spectrum of CCP-G, which shows that the copper ion is converted from divalent to monovalent after the reaction of CCP and GSH; Figure H is the ability of CCP-G to produce ROS detected by TMB; Figure I is the ERS electron spin resonance image under DMPO capture agent (capture ·OH), indicating that CCP-G has a stronger ability to produce ROS than CCP.
[0081] Comparative Example 2:
[0082] First, PLA powder was melted and extruded using an extruder at a speed of 45 mm s -1The PLA filament was then stretched at an appropriate speed to obtain a filament with a diameter of 1.75 mm. The PLA filament was then heated to a set temperature of 215 °C in an electric field-driven bio-3D printer (BIO-EM3DP15A) and stretched at a speed of 10 mm s -1 The PLA scaffolds were extruded through a 250 μm nozzle at a speed of 100 μm to fabricate the PLA scaffolds. The scaffolds were rinsed three times with deionized water to remove surface impurities, dried in a vacuum oven at 60 °C, and then cut into PLA cylindrical scaffolds with a diameter and height of 3.5 mm using a 3.5 mm punch.
[0083] Comparative Example 3
[0084] (1) Preparation of GelMA: 10 g of pig skin gelatin was added to 100 mL of PBS, and the mixture was magnetically stirred at 50°C for 1 hour. Then 8 mL of methacrylic anhydride (MA) was added dropwise to the gelatin solution and stirred at 50°C for 3 hours. The reaction was terminated by adding an equal amount of PBS preheated to 50°C to the above mixture. The reaction solution was dialyzed in deionized water using a dialysis bag (molecular cutoff 8-14KD) for 8 days to remove MA, and the solution was filtered and freeze-dried to obtain methacrylate gelatin.
[0085] (2) Preparation of GBS: 0.5 g of GelMA and 10 mg of LAP were dissolved in 5 mL of deionized water to obtain solution A. 0.4 g of sodium alginate and 0.2 g of borax were dissolved in 5 mL of deionized water and stirred at 40°C until the sodium alginate was completely dissolved to obtain solution B. Solution A was then stirred and mixed into solution B to obtain a double cross-linked hydrogel solution GBS.
[0086] like Figure 3 As shown, the prepared composite scaffold was characterized. Figures A and B are the SEM images and element distribution images of the PLA scaffold and the PH scaffold, respectively, which show that nHA was successfully modified on the PH scaffold. Figure C is the mechanical property analysis of the scaffold, which shows that the modification of nHA did not significantly reduce the elastic modulus of the scaffold; Figures D and E are the evaluation of the hydrophilicity of the scaffold by the sessile drop method water contact angle, which shows that the modification of nHA improves the hydrophilicity of the scaffold; Figure F is the SEM image and element distribution of the PH-GBS@CCP scaffold; Figure G is the CCP drug release curve of the PH-GBS@CCP scaffold under different microenvironments.
[0087] Application Example 1:
[0088] Verification of the killing effect of composite scaffolds on tumor cells in vitro:
[0089] CCP was labeled with fluorescent substance FITC and incorporated into the scaffold. The scaffold was co-cultured with tumor cells, and the phagocytosis of CCP by cells was observed under a fluorescence microscope. Figure 4As shown in A, the amount of CCP phagocytosis by tumor cells is greater than that of CC. Different composite scaffolds were co-cultured with tumor cells and CCK-8 ( Figure 4 B) and dead / live staining ( Figure 4 C) Analysis of tumor cell killing activity showed that PH-GBS@CCP had the strongest tumor killing effect. Figure 4 D shows that PH-GBS@CCP has the strongest inhibitory effect on tumor cloning and invasion. Different composite scaffolds were co-cultured with tumor cells (143B and U2OS), and tumor cells were collected and 7-AAD / PI apoptosis staining was performed. The proportion of apoptotic cells was detected by flow cytometry. The results are shown in Figure 4 As shown in E-4H, compared with the control group, the proportion of tumor cell apoptosis was the highest after co-culture of PH-GBS@CCP and tumor cells.
[0090] Application Example 2:
[0091] Verification of the tumor-killing effect of the composite scaffold in the nude mouse orthotopic osteosarcoma model:
[0092] First, Luc-labeled 143B cells were injected subcutaneously into nude mice to form subcutaneous tumors. The subcutaneous tumors were removed and divided into small pieces with a diameter of about 1 mm. 3 A wedge-shaped notch was cut at the proximal end of the nude mouse tibia, and the small tissue block was implanted into the notch of the tibia. The skin was sutured. On the tenth day, the tumor tissue visible to the naked eye was removed with a scalpel and different scaffolds were implanted. The schematic diagram of the nude mouse experiment is shown in the figure. Figure 5 As shown in A. Since tumor cells carry the Luc gene, the tumor tissue will emit fluorescence after the fluorescent substance is injected into the mouse peritoneal cavity. In the three weeks after the implantation of the scaffold, the tumor fluorescence intensity is observed every week, as shown in Figure 5 B and Figure 5 As shown in C, the tumor fluorescence and tumor volume of PH-GBS@CCP after implantation are the smallest, indicating that it almost inhibits tumor recurrence. Figure 5 E shows the survival curves of the four groups of nude mice. All the nude mice treated with PH-GBS@CCP survived. Within 3 weeks of stent implantation, the weight of the nude mice in the stent implantation group was comparable to that of the control group ( Figure 4 D), indicating that the scaffold has no obvious biological toxicity. In the third week, we performed CT scans on the tibia of nude mice bearing tumors. Figure 5 F shows that the tibiae of nude mice without nanodrug treatment had obvious osteolytic changes, while the tibiae of the PH-GBS@CCP scaffold group were the most intact.
[0093] Application Example 3:
[0094] Exploration of the tumor-killing mechanism and verification of the anti-lung metastasis effect of the composite scaffold in the nude mouse orthotopic osteosarcoma model:
[0095] In the third week after tumor resection, we removed lung tissues from nude mice after injecting luciferin, e.g. Figure 6 A and 6H show that no metastatic lesions were found in the lung tissues of PH-GBS@CCP mice. The lung tissues were pathologically sectioned and stained with H&E ( Figure 6 B), illustrates the anti-metastasis effect of the composite scaffold. Figure 6 C is H&E staining of tibial orthotopic tumor ( Figure 5 C), CCP caused tumor cells to undergo apoptosis, and Tunel staining also confirmed this result ( Figure 5 D and 5I). Ki67 is an indicator of tumor cell proliferation. Figure 6 E and Figure 6 J showed that compared with the control group, the expression of Ki67 was significantly decreased after PH-GBS@CCP treatment. In addition, by immunofluorescence staining of tumor tissue Dlat and Fdx1 (both are indicators of copper death), Figure 6 F. Figure 6 G indicates that the composite scaffold containing nanodrugs triggers the copper death effect of tumor tissue.
[0096] Application example 4:
[0097] Effect of composite scaffold on osteogenesis in rat femoral condyle defect model:
[0098] like Figure 7 As shown in A, the lateral femoral condyle of the rat was exposed, and a cylindrical bone defect with a diameter of 3.5 mm and a depth of 3.5 mm was made on the lateral condyle, and the composite scaffold was implanted therein. The rat femoral specimens were taken out at the 4th and 8th week of the operation, and CT scanning three-dimensional reconstruction was performed. Figure 6 B shows that the PH-GBS@CCP group formed the most bone tissue at the defect site. CT data analysis showed that BV / TV ( Figure 7 C) and trabecular separation ( Figure 7 D) The results in the PH-GBS@CCP group were the best. Figure 7 E and Figure 7 F shows the H&E staining and Masson staining of the rat femoral condyle tissue section. The results show that at the 8th week, the bone defect in the composite scaffold was almost completely filled with mature bone tissue, while the control scaffold was partially filled with fibrous tissue and immature bone tissue. In addition, the OCN ( Figure 7 G) and OPN( Figure 7 H) Immunofluorescence staining of two proteins (markers of osteogenesis) showed that the composite scaffold had the most obvious osteogenesis effect.
[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a composite scaffold for promoting the repair of bone defects after bone tumor surgery, characterized in that: The following steps are involved: Step 1: Preparation of nanohydroxyapatite-modified polylactic acid 3D printed scaffold (PH); Step 2: cRGD fk -PEG 2K - Preparation of DSPE-modified copper-cysteine nanoparticles (CCP); Step 3: Preparation of methacrylate gelatin GelMA; Step 4: dissolving the CPP and photoinitiator prepared in step 2 in deionized water, and dissolving the GelMA prepared in step 3 into the above solution to obtain solution 1; Step 5: Dispersing borax and sodium alginate SA in deionized water to obtain solution 2; Step 6: Mix solution 1 with solution 2 in a stirring state to obtain solution 3 after mixing evenly; Step 7: Fill the solution prepared in step 6 into the PH scaffold prepared in step 1, and expose the scaffold to ultraviolet light to solidify the hydrogel to form a composite scaffold.
2. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: The step 1 is specifically as follows: Step 1.1: First, PLA powder was melted and extruded using an extruder and stretched at an appropriate speed of 40-50 mm / s to obtain a filament with a diameter of 1.75 mm; Step 1.2: Then, the PLA filament was heated to a set temperature of 215 °C in an electric field-driven biological 3D printer BIO-EM3DP15A and extruded through a 100-1000 μm nozzle at a speed of 6-10 mm / s to fabricate the PLA scaffold; Step 1.3: Rinse the scaffold three times with deionized water to remove surface impurities, dry the scaffold in a vacuum oven at 60 °C, and then cut it into cylindrical scaffolds with a diameter and height of 3.5 mm using a 3.5 mm punch; Step 1.4: The scaffold was then immersed in an ammonia solution with a pH of 12.5 and magnetically stirred at room temperature; finally, the scaffold was immersed in 1% w / v nanohydroxyapatite nHA / ethanol and stirred for 1 hour, washed with deionized water, and naturally air-dried to obtain nHA-modified PLA scaffold PH, in which the molecular weight of PLA was 80 KDa.
3. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: The step 2 is specifically as follows: Step 2.1: Dissolve sodium hydroxide and L-cysteine in deionized water to obtain solution A; Step 2.2: Then, cupric chloride dihydrate was dissolved in deionized water; an equal volume of solution A was added dropwise to the cupric chloride solution, stirred at 500 rpm for 5 minutes to form copper-cysteine nanoparticles, and the precipitate was collected by centrifugation at 6000 rpm for 3 minutes, and then the product was washed three times with water and anhydrous ethanol respectively, and cRGD fk -PEG 2k -DSPE was dissolved in DMSO (15 mg / mL); Step 2.3: An equal volume of CC NPs ethanol solution (15 mg / mL) was added to the above solution. After the mixture was stirred at 4 °C for 6 h, it was centrifuged (6000 rpm, 10 min) to collect CCP; the concentration of sodium hydroxide was 8 g / L, the concentration of L-cysteine was 24.2 g / L, the concentration of copper chloride dihydrate was 17 g / L, and the concentration of cRGD was 1. fk -PEG 2k -DSPE concentration was 15 mg / mL.
4. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: The step 3 is specifically as follows: Step 3.1: 10% w / v pig skin gelatin was added to PBS and the mixture was magnetically stirred at 45-55°C for 1 hour; then 8-10 mL of methacrylic anhydride (MA) was added dropwise to the gelatin solution and stirred at 50°C for 3 hours; Step 3.2: Add an equal amount of PBS preheated to 50°C to terminate the reaction. The reaction solution is dialyzed in deionized water using a dialysis bag (molecular cutoff 8-14KD) for 7-10 days to remove MA. The solution is filtered and freeze-dried to obtain methacrylate gelatin.
5. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: In step 4, the concentration of CCP is 0.1-1% w / v; the concentration of borax is 1-4% w / v; the concentration of GelMA is 5-10% w / v; the concentration of sodium alginate is 4% w / v; the photoinitiator is one of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or 2,4,6-trimethylbenzoyl lithium phosphite, and the concentration of the initiator in the system is 0.1-1% w / v.
6. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: In step 5, the concentration of borax is 2% w / v; the concentration of sodium alginate is 4% w / v; the two are stirred at 40-60° C. for 1-4 hours to completely dissolve the borax and sodium alginate in deionized water.
7. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: In step 6, the ratio of solution 1 to solution 2 is 1:1, the stirring condition is 400 rpm, and the stirring time is 10 minutes.
8. The method for preparing a composite scaffold for promoting bone defect repair after bone tumor surgery according to claim 1, characterized in that: The volume of solution three used in step 7 is 15 μL, the wavelength of ultraviolet light is 300-400 nm, and the curing time is 3-5 minutes.
9. The use of the composite scaffold for promoting bone defect repair after bone tumor surgery according to any one of claims 1 to 8, characterized in that: Application in bone defect repair after osteosarcoma surgery.